2013
DOI: 10.1093/eurpub/ckt033
|View full text |Cite
|
Sign up to set email alerts
|

Manganese concentrations in maternal and umbilical cord blood: related to birth size and environmental factors

Abstract: Our results suggested that lower or higher Mn level in maternal and umbilical blood may induce adverse effect on birth size in humans. In addition, increased levels of Mn in MWB or UCB may be associated with exposure to some environmental hazard factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 31 publications
3
40
5
Order By: Relevance
“…However, these concentrations were much lower than those reported in comparable studies from China (mean 55 µg/L) and France (mean 23 µg/L) 31,32 . Mn levels at different stages of pregnancy were not reported in the current study.…”
Section: Discussioncontrasting
confidence: 76%
“…However, these concentrations were much lower than those reported in comparable studies from China (mean 55 µg/L) and France (mean 23 µg/L) 31,32 . Mn levels at different stages of pregnancy were not reported in the current study.…”
Section: Discussioncontrasting
confidence: 76%
“…While the function of the fifth gene region, LOC284276 , is not currently known, we found that the placental methylation status of cg22284422 within this region was significantly associated with birth weight. The mechanism responsible for the association between methylation of this loci and birth weight is unknown, but it has been suggested that Mn levels in maternal and umbilical cord blood are linked to impaired fetal growth 4749 . The absence of data characterizing this putative gene limit our ability to understand the nature of this association, but GEO datasets report LOC284276 expression changes to occur in colorectal cancer, prostate cancer, glial brain tumors, and adult acute myeloid leukemia 50 suggesting that it has an important role in growth and development.…”
Section: 1 Discussionmentioning
confidence: 99%
“…In Shanghai study [20], they found that maternal Mn was associated with birth weight (n = 175, mean of maternal whole blood Mn = 6.6 μg/dL, mean of umbilical cord blood Mn = 8.5 μg/dL). In Dalian city study [21], northern China, significant relationship was observed between cord blood Mn and birth weight (n = 125, mean of maternal whole blood Mn = 55.0 μg/L, mean of umbilical cord blood Mn = 78.8 μg/L). The former study found that the birth weight increased Mn levels up to 4.18 μg/dL, the peak point of the latter study was 90.0 μg/L, and then decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The authors examined the relationship between cord serum Mn and birth weight by multiple regression, and did not find a significant association between them, although they found a negative relationship and nonlinear relationship between cord serum Mn and birth length and Ponderal index, respectively [23]. Because blood Mn level in the cord blood is higher than that in maternal blood at the time of delivery [20,21] and this study was conducted with serum, it cannot be directly comparable to our study.…”
Section: Discussionmentioning
confidence: 99%